The Role of Micro, Small and Medium Enterprises in Reducing Unemployment in Lampung Province - Mervita, Eda; Hasanuddin, Hasanuddin; Rumianti, Susti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
In the current era of globalization, there are many different types of businesses that can be found in Indonesia, both on a small and large scale. In this case, the government always strives to provide support for MSMEs so that they can create thriving businesses in each of their respective fields. The data analysis used is multiple linear regression. The research results show that: 1) The wage level and the F Test for Micro, Small and Medium Enterprises both have a simultaneous influence on unemployment in Lampung Province . 2) Based on the findings of a partial test (t test) comparing SMEs, the response rate in East Java Province has decreased. This can be explained by the calculated t value of 27.85499 but the t table value is only 2.13185. The calculated t value obtained exceeds the t table significantly, or the significance level of 0.00 is smaller than 0.05. Action in Lampung Province will decrease by 22.2% with the growth of micro and small businesses, according to the regression coefficient of 0.222454 or 22.2%. 3) The level of wages in MSMEs has a negative impact on reducing income in Lampung Province , according to the partial test (t test) between them. This can be explained by the fact that the calculated t value, namely -7.082008, is substantially smaller than the t table value, 2.13185, or by using a significant threshold of 0.0021 < 0.05. The response rate in Lampung province will decrease by 3.92% when the wage rate for micro, small and medium enterprises is increased, according to the regression coefficient of -3.920577, or 3.92%. Keywords: Unemployment, wage level, MSMEs